(untitled)
An au.empt was made to assess the genetic diversity am(mg the eUte selections c0Uec1c:d from the na1Ural pOpulations in semj-arid pans of Gujarat. A toial of lO accessions of mahtia (Madlmca longifolin) were subjected to RAPO profiling using JO primers (OPF). The d.na from all primers wen: p00led and subjected LO analysis through Nc:i and Li’s c.oefficien1. The results demons1rmed Lha1 a wide genetic "ariabil.ity exjs1s in the naiural population or rnahua growing in semi ;).rid pMtS of the Gujarn1. This needs to be con.Cr\’cd